Fungal diversity associated with bamboo litter from Bambusetum of Rain Forest Research Institute, Northeast India - RAJESH KUMAR; ASHWANI TAPWAL; SHAILESH PANDEY; RAJA RISHI (Society for Indonesian Biodiversity, 2013)
Kumar R, Tapwal A, Pandey S, Rishi R. 2013. Fungal diversity associated with bamboo litter from Bambusetum of Rain Forest Research Institute, Northeast India. Biodiversitas 14: 79-88. Fungi play an important role in leaf litter decomposition due to their ability to break down the lignocelluloses matrix, which other organisms are unable to digest. Diversity of bamboo leaf litter fungi from fallen leaves and undergoing active decomposition leaves in different season and different depth was carried out in 2009-10. Twenty four samples were collected from Bambusetum of Rain Forest Research Institute (RFRI), Northeast India. The moist chamber, direct isolation and dilution plate methods were used to assess the diversity of fungal species. Fungi were cultivated on 3% malt extract agar and half strength potato dextrose agar. The litter was divided into freshly fallen senescent leaves (grade 1) and leaves already undergoing active decomposition (grade 2). Moist chamber incubation of the litter revealed 45 fungal taxa belonging to 22 genera. fungal taxa were found on grade I and 39 fungal taxa found on grade II litter. Although 24 fungal taxa were common to both grades, Differences were observed in percentage occurrence of fugal species between the two grades of litter. Periodic surveys were carried out to collect macrofungi. Young and matured carpophores of 16 macro fungi species were collected in different seasons. Out of these macrofungi, 3 species belongs to family Entolomataceae and Agaricacea, two species belongs to Tricholomataceae and Geoglossaceae one species belongs to each family Dacrymycetaceae, Pluteaceae, Coprinaceae, Marasmiaceae Lycoperdaceae and Phallaceae. The bamboo leaf-litter was selected for the present syudy because of the dominance and great economic value of bamboo vegetation in North-east India.